Minocycline as an alternative in the treatment of pulpotomy in temporary teeth - Orellana Centeno, José Eduardo (2019)
Objetive. To determine the effectiveness of the minocycline gel prolonged release as an antimicrobial agent in the treatment of pulpotomy in child and the effectiveness of the minocycline applied as a drug in the treatment of pulpotomy. Methods. Pulpotomy treatment was perfomed in 39 dental samples according to the technique described by Sweet et al., before and after the minocycline drug was placed. A sample was taken (paper tip placement) and microorganisms were counted, by plate counting method. Results. A clinical and radiographic review was performed at 15, 30, 90 and 180 days. The results were recorded according to the clinical and radiographic instrument of the American Pediatric Dentistry Association (AAPD). There were three cases of failure, representing only 8%, with 92% success in this treatment. Conclusions. It was concluded that the medication with minocycline is a valuable auxiliary in the local disinfection of the pulp chamber and therefore for the treatment of pulpotomies.